2012
DOI: 10.1152/japplphysiol.00988.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular and corticomotor function during progressive passive hyperthermia in humans

Abstract: The present study examined the integrative effects of passive heating on cerebral perfusion and alterations in central motor drive. Eight participants underwent passive hyperthermia [0.5°C increments in core temperature (Tc) from normothermia (37 ± 0.3°C) to their limit of thermal tolerance (T-LIM; 39.0 ± 0.4°C)]. Blood flow velocity in the middle cerebral artery (CBFv) and respiratory responses were measured continuously. Arterial blood gases and blood pressure were obtained intermittently. At baseline and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
80
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 40 publications
9
80
2
Order By: Relevance
“…The increase in peak muscle relaxation supports previous observations made during brief (Ross et al 2012) and sustained MVCs (Todd et al 2005) performed during passive hyperthermia. Our results extend these observations to indicate that despite the development of peripheral fatigue as a result of exercise, the rate of muscle relaxation also increases during ExH in response to a rise in whole-body temperature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in peak muscle relaxation supports previous observations made during brief (Ross et al 2012) and sustained MVCs (Todd et al 2005) performed during passive hyperthermia. Our results extend these observations to indicate that despite the development of peripheral fatigue as a result of exercise, the rate of muscle relaxation also increases during ExH in response to a rise in whole-body temperature.…”
Section: Discussionsupporting
confidence: 90%
“…The decline in force production capacity and voluntary activation noted during the brief MVCs on reaching SEV-ExH and SEV-PaH (Table 2) supports previous observations (Morrison et al 2004;Thomas et al 2006;Racinais et al 2008;Périard et al 2011a,b;Ross et al 2012). It was anticipated that a larger decline in brief MVC force output would occur during MOD-ExH compared with MOD-PaH due to development of peripheral muscle fatigue.…”
Section: Brief Contractionssupporting
confidence: 84%
“…In the current study, inhaling a hypercapnic gas mixture restored MCAv mean to pre-LBNP values. Previous studies have shown that in heat-stressed individuals returning PETCO 2 to isocapnic values only partially restores MCAv mean when supine or seated (4,11,33). Thus other modulators of cerebral perfusion, such as reductions in perfusion pressure or an increased sympathetic activity, seemingly contribute to heat-related reductions in MCAv mean (3).…”
Section: Discussionmentioning
confidence: 97%
“…While the mechanisms underlying this impaired tolerance are not fully elucidated, it is clear that hyperthermia reduces cerebral perfusion at rest (4,10,29,40) and that these reductions are exacerbated during a hypotensive perturbation (i.e., tilt or stand) (25,40). Hyperventilation and related reductions in end-tidal CO 2 (PETCO 2 ) are purported to contribute to at least 50% of said reductions in cerebral perfusion (4,11,29,33). As such, inhaling a hypercapnic gas mixture and elevating cerebral perfusion should improve tolerance to a hypotensive challenge, given that cerebral hypoperfusion ultimately results in syncope (38).…”
mentioning
confidence: 99%
“…Ross and colleagues recently evoked motor potentials from the vastus lateralis measured in parallel with cerebral blood flow velocity (CBFv) during progressive passive hyperthermia to 39° C (Ross et al, 2012). CBFv and cortical voluntary drive both decreased with core temperatures elevated 0.5–2.0°C; however, corticospinal excitability measured by the MEP response to TMS was unaltered.…”
Section: Discussionmentioning
confidence: 99%